The Impact of Ratification and Implementation of the Convention on International Sales of Goods (CISG) on Indonesia's International Trade and Business Activities - Achmad Fata Altika; Mahmul Siregar; Joiverdia Arifyanto (Universitas Efarina, 2025)
This study was conducted with the aim of identifying and analyzing the role of the international convention on the sale of goods or the Convention International Sales of Good (CISG) on the international trade and business activities of Indonesia. The implementation of international business has its own obstacles that are different and more difficult to face than the obstacles in the domestic market. International sale and purchase of goods is a very important area of ​​law in the era of globalization, especially in supporting activities in the international trade and business transaction sector. CISG includes material on the formation of international contracts which aims to eliminate the need to indicate the laws of a particular country in international trade contracts and to facilitate the parties in the event of a conflict between legal systems. To overcome the obstacles that can arise from the diversity of legal systems, the international trade community in 1988 created an international convention to regulate international sale and purchase agreements. The convention is known as The United Nations Convention on Contracts for the International Sale of Goods (CISG). CISG can function to overcome obstacles that arise from the diversity of legal systems. Indonesia needs to ratify the convention as soon as possible for the welfare of the Indonesian nation and the legal certainty of business actors.